Internationalisation and economic growth: the Portuguese case - Lopes da Costa, R.; António, N. (XXVII Jornadas Hispano-Lusas. Alicante 2017, 2017)
Historically, a policy of enforcement in internationalisation processes is still seen by many as an approach to solve certain economic crises. However, Portugal’s solution for this problem is part of a greater problem, namely trying to solve a European problem that has recently worsened and is largely uncontrolled. This article aims to contribute, firstly by mentioning the Portuguese economic context and also possible ways of internationalisation and, secondly, by measuring a set of variables/factors that should support the development of the Portuguese economy. The results of the interviews which supported this study’s methodological basis show that the Portuguese economy’s poor dynamism and low demand by alternate markets are the two critical variables for the country’s weak competitiveness. The suggestions of those surveyed propose that the Portuguese economy’s dynamics should be characterised by a hybrid model, joining factors connected to the Nordic school’s behavioural model, Dunning’s eclectic paradigm (1997), and Buckley and Casson’s model of internationalisation theory (1976).